Discurso camuflado : uma análise crítica e multimodal do anúncio "Confissões de camuflagem" - Cavalcanti, Camilla Reisler (2016)
In the contemporary world of communication, understanding and explaining the impact of a discourse is a complex ordeal. There is a narrowing of borders in which the time-space relation defies social stabilities. Social representations and interactions take place beyond geographic communities, since new, virtual communities are created many times according to economic interests and consumer habits. Questions that guide this research are: How are these groups created and who dominates them? Under which criterion are they defined? What is the role of the media in society and how do ads keep the power position of companies? Which discursive strategies are applied for such goal? In search of these answers, this research analyses how the discourse of a YouTube video ad strengthens the domination of a market sector under one sole company, at the same time it construes a positive social representation of the company. The Dermablend brand launched a campaign with the title “Camo Confessions”. For our corpus, we´ve chosen three video ads produced by the agency and two home videos posted as replies to the campaign. This choice is justified for the videos provide examples of a new way of discursive social practice, in which the genre is redesigned. We plan to show how constitutive characteristics of the genre´s discourse reinforce the beauty ideology by means of social representation and maintenance of elite hegemony. We start with the hypothesis that such discourses are manipulative, controlling consumers´ behavior who surrender themselves to the ideology of the cosmetic industry, but nevertheless feel that are free and responsible for their choices. We draw upon the sociocognitive approach of Critical Discourse Analysis (VAN DIJK, 1998, 2012a, 2012b, 2014) allied to the Theory of Multimodality (KRESS; VAN LEEUWEN, 2001, 2006, VAN LEEUWEN, 2008, KRESS, 2010). The results point to the fact that there was not only manipulation of consumers´ behavior, but also the inclusion of a minority group which previously wasn´t legitimated to be part of the community of users of beauty products, contributing to the hegemonic position of the company.